2016
DOI: 10.1080/07929978.2016.1151286
|View full text |Cite
|
Sign up to set email alerts
|

Influence of organic and mineral-based conventional fertilization practices on nutrient levels, anti-proliferative activities and quality of sweet red peppers following cold storage

Abstract: The demand for organic food products has increased over the last decades; however, the health effects of organically grown products are controversial and knowledge about how different fertilization regimes affect nutritionally and health relevant components is still limited. The aim of the present study was to determine the effect of organic and conventional mineral-based fertilizers on the quality of sweet red peppers. The parameters tested were anti-proliferative activity against cancer cells and the concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
1
3
0
1
Order By: Relevance
“…In recent work, we reported that the contents of vitamin C, hydrophilic antioxidants and total phenolics in sweet bell pepper were not significantly affected by storage (Elmann et al, 2016;Lama et al, 2016). Our current results suggest that prolonged storage has an accession-specific effect on the content of the health-promoting phytonutrients in chilli peppers.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…In recent work, we reported that the contents of vitamin C, hydrophilic antioxidants and total phenolics in sweet bell pepper were not significantly affected by storage (Elmann et al, 2016;Lama et al, 2016). Our current results suggest that prolonged storage has an accession-specific effect on the content of the health-promoting phytonutrients in chilli peppers.…”
Section: Discussionsupporting
confidence: 42%
“…In a previous work, we have determined the levels of similar phytochemicals in sweet red peppers (Elmann et al, 2016). Comparing the data, accession 1745 had eightfold higher levels of flavonoids, and higher antioxidant capacity relative to sweet red peppers.…”
Section: Discussionmentioning
confidence: 98%
“…Phytonutrients such as vitamin C or AOX capacity are increasingly important aspects of fruit quality because they are associated with benefits to consumer's health [29], and pepper is considered as one of the healthier fruits [30]. Antioxidant synthesis and accumulation in plants is generally stimulated by biotic or abiotic stress such as salinity; they can protect plant organs from serious oxidative damage to lipids, proteins, and nucleic acids [22].…”
Section: Discussionmentioning
confidence: 99%
“…La importancia del conocimiento de los antioxidantes se debe a que, además de que afecta la vida útil de los frutos y vegetales, estos son capaces de proteger a las células contra los radicales libres causantes de enfermedades crónico-degenerativas, entre ellas el cáncer (Elmann, Garra, Alkalai-Tuvia & Fallik, 2016), y su consumo podría ejercer un impacto benéfico sobre la salud de los humanos.…”
Section: Discussionunclassified